Mitochondria: A Covert Chronic Infection Masquerading as a Symbiotic Partner? - George B. Stefano (Frontiers in Bioscience-Landmark, 2025)
Mitochondria, ubiquitous in eukaryotic cells, evolved from an ancestral aerobic alpha-proteobacterium that had been phagocytosed by a primordial archaeal cell. Numerous factors link mitochondria to current-day bacteria, notably the facultative pathogens that are phagocytosed and survive within the host as a chronic infection. Despite these parallels, we typically refer to mitochondria as “symbionts” and rarely consider them as perhaps the most successful example of long-term chronic infection. Here, we will explore critical aspects of mitochondrial structure and function and consider what we might learn by refocusing our attention on mitochondria as bacteria that are uniquely adapted to their host cell, i.e., as a chronic infection tolerated by its eukaryotic host.